Experimental study on the optimization of general conditions for a free-flow electrophoresis device with a thermoelectric cooler - Yan, Jian; Yang, Cheng-Zhang; Zhang, Qiang; Liu, Xiao-Ping; Kong, Fan-Zhi; Cao, Cheng-Xi; Jin, Xin-Qiao (Journal of separation science, 2014)
With a given free‐flow electrophoresis device, reasonable conditions (electric field strength, carrier buffer conductivity, and flow rate) are crucial for an optimized separation. However, there has been no experimental study on how to choose reasonable general conditions for a free‐flow electrophoresis device with a thermoelectric cooler in view of Joule heat generation. Herein, comparative experiments were carried out to propose the selection procedure of general conditions in this study. The experimental results demonstrated that appropriate conditions were (i) <67 V/cm electric field strength; (ii) lower than 1.3 mS/cm carrier buffer conductivity (Tris‐HCl: 20 mM Tris was titrated by HCl to pH 8.0); and (iii) higher than 3.6 mL/min carrier buffer flow rate. Furthermore, under inappropriate conditions (e.g. 400 V voltage and 40 mM Tris‐HCl carrier buffer), the free‐flow electrophoresis separation would be destroyed by bubbles caused by more Joule heating. Additionally, a series of applications under the appropriate conditions were performed with samples of model dyes, proteins (bovine serum albumin, myoglobin, and cytochrome c), and cells (Escherichia coli, Streptococcus thermophilus, and Saccharomyces cerevisiae). The separation results showed that under the appropriate conditions, separation efficiency was obviously better than that in the previous experiments with randomly or empirically selected conditions.